Da'wah Based Spiritual Counseling: The Urgency of Spirituality Development for Correctional Inmates in Lembaga Pemasyarakatan Kelas I Cirebon - Suteja, Jaja; Setiawan, Bambang (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
This research was motivated by the trend of the increase of problems experienced by correctional inmates which prompted the need for guidance and counseling services, especially preaching-based spiritual counseling services. Da'wah-based spiritual counseling exists as a form of moral and spiritual commitment and responsibility in helping inmates as individuals who need assistance. This research aims to obtain a comprehensive analytical review of preaching-based spiritual counseling in Lembaga Pemasyarakatan Kelas I Cirebon which can be used to develop the spirituality of the correlational inmates. A qualitative research approach was used with library research methods by summarizing various relevant research results regarding spiritual counseling which can be used narratively in developing new theories and complementing previous theories regarding preaching-based spiritual counseling. This research obtained results in the form of an intervention mechanism for preaching-based spiritual counseling services at the Lembaga Pemasyarakatan Kelas I Cirebon to help inmates alleviate emotional suffering and develop spiritual well-being. Da'wah-based spiritual counseling in developing the spirituality of the inmates is provided through therapeutic ritual-personal activities which are carried out through five stages, namely centering and grounding, assessment, gathering energy, directing the energy, and gratitude and closure.